Aorta vascular stent structure capable of absorbing polyester material

By using absorbable polymer polyester materials to prepare aortic vascular stents with different shapes, the problem of mismatch between the stent shape and the aortic vessels in the prior art is solved, and the good fit between the stent and the aortic wall is achieved and Reduced risk of internal leakage.

CN222487748UActive Publication Date: 2025-02-18JILIN UNIVERSITY
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202420830537.X
Authority / Receiving Office
CN · China
Patent Type
Utility models(China)
Current Assignee / Owner
Filing Date
2024-04-22
Publication Date
2025-02-18
Estimated Expiration
2034-04-22

AI Technical Summary

Technical Problem

In the prior art, the polyester polymer material of coronary artery blood vessels biodegradation of the human absorption stent shape does not match the aortic blood vessels, resulting in poor fit between the stent and the proximal end of the aorta, increasing the risk of endospermia and reverse-stripping aortic dissection. .

Method used

Aortic vascular stents are prepared using absorbable polymer polyester materials, and the mesh structures of different shapes are formed through extrusion processing and laser engraving, such as Z-shaped bridge, honeycomb, oval, rhombic, wavy and spiral sinusoidal curves. to adapt to different vascular lesions and surgical needs.

Benefits of technology

The matching of the stent shape and the aortic vessels is achieved, the fit between the stent and the aortic wall is enhanced, the risk of endospermia and reverse-stripping aortic dissection is reduced, and good mechanical support and biocompatibility is provided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN222487748U_ABST
    Figure CN222487748U_ABST
Patent Text Reader

Abstract

The utility model discloses an aorta vascular stent structure capable of absorbing polyester materials. The absorbable polymer polyester material is extruded into a pipe, and the outer diameter of the pipe is 22-46 mm; the thickness of the pipe wall is 0.4-1.5 mm; the pipe is subjected to laser engraving to form the absorbable bare stent with the netted wires; the diameter of the net silk is the same as the wall thickness of the absorbable polyester tube; and the length of the tubular additional bracket is 60-180 millimeters. The pipe can form a Z-shaped, honeycomb-shaped, oval, diamond-shaped, wave-shaped, spiral sine curve-shaped and other net wire structures through laser engraving; the stent can be used as an additional stent to provide proper mechanical support for the aorta covered stent, and the requirements of strength, toughness and human body absorption and degradation are met; the shape and the size of the device are matched with those of the aortic vessel, so that the pain of a patient is reduced, the function is effective, and the risks of internal leakage of the aortic vessel and reverse dissection of aortic dissection are eliminated; and specific vasculopathy characteristics and operation requirements are met to the maximum extent, so that the optimization of the treatment effect is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The utility model belongs to the technical field of medical equipment, and relates to an aortic vascular stent structure made of absorbable polyester material. The utility model is particularly suitable for thoracic aorta intracavitary isolation and abdominal aorta intracavitary isolation in cardiovascular surgery. Background Art

[0002] In the field of cardiovascular surgery, thoracic aortic endovascular exclusion has become one of the main methods for treating thoracic aortic diseases such as thoracic aortic dissection, thoracic aortic aneurysm, and thoracic aortic penetrating ulcer. Abdominal aortic endovascular exclusion has become one of the main methods for treating abdominal aortic diseases such as abdominal aortic aneurysm and abdominal aortic dissection.

[0003] The incidence of endoleak after metal-covered stent implantation is 10%-44%. According to the cause and location, endoleak is generally divided into types I-IV. Type I endoleak refers to the continuous flow of blood into the aneurysm cavity from the gap between the proximal or distal end of the graft and the arterial wall. Type II endoleak refers to the continuous blood flow through unobstructed collateral vessels, such as the lumbar artery, inferior mesenteric artery, internal iliac artery, etc., and reverse flow into the aneurysm cavity. Type III endoleak refers to endoleak caused by poor connection or dislocation between stent components. Type IV endoleak refers to the continuous flow of blood into the aneurysm cavity through the pores of the graft. Postoperative arterial endoleak can cause the false lumen of the dissection to continue to expand, reducing the therapeutic effect of the operation; severe cases can lead to the formation of thoracic and abdominal aortic aneurysms, tearing of the inner wall of the blood vessels, and reverse aortic dissection, thereby increasing the risk of rupture of distal thoracic and abdominal aortic aneurysms and aortic rupture.

[0004] Absorbable biomedical materials as artificial vascular stents have been widely studied and applied to a certain extent in coronary artery surgery; however, their mechanical strength and toughness are inferior to those of metal materials, and the acidic products after degradation are prone to inflammation; therefore, they have not been attempted to be studied and applied in the field of aortic diseases.

[0005] One of the fundamental reasons for postoperative endoleak is the poor fit between the stent and the proximal aorta, which may be caused by the complexity of the anatomical structure, the inadequate stent design, or improper placement technique during surgery. The shape and size of the artificial vascular stent should be adapted to the size of the blood vessel; if the shape is not good or the size is too small, it will not provide sufficient mechanical support; if the artificial vascular stent is not firmly clamped, it will wander, slip, and leak under the impact of aortic blood pulsation, which will endanger the patient's life safety; if the shape is not good or the size is too large, it will increase the patient's pain. What is more serious is that the patient's artery is aging and lacks elasticity. If the shape is not good or the size is too large, it may cause vascular tearing, which may seriously cause reverse aortic dissection.

[0006] The coronary arteries are small, while the aorta is large. The biodegradable and body-absorbable polyester stents used in the coronary arteries are much smaller than the aorta and cannot provide clamping support. They cannot be used in aortic surgery.

[0007] In order to treat thoracic aortic aneurysm, thoracic aortic dissection, abdominal aortic aneurysm, and abdominal aortic dissection, and effectively prevent the high incidence of endoleak after thoracic aortic / abdominal aortic metal covered stent implantation, the current technology focuses on how to strengthen the radial support force of the proximal end of the covered stent and improve its fit with the aortic vessel wall, fundamentally preventing the occurrence of endoleak, reverse aortic dissection, and distal aneurysm. However, as of now, no ideal solution has been developed, and only a few patents provide solutions, but all of them have certain limitations.

[0008] Patent CN110721007A: Barbs are set on the outer wall of the stent: the blood vessel wall is easily damaged when the stent moves; the interaction between the barbs and the blood vessel wall leads to chronic inflammation and increases the risk of vascular complications.

[0009] Patent CN218391850U balloon dilatation method: adjust the position and shape of the stent through balloon dilatation technology to reduce or eliminate endoleak. However, since the edge of the stent is very fragile, excessive dilatation can easily cause additional damage to the blood vessel wall; the dilatation process may cause new intimal tears, which may seriously cause reverse aortic dissection.

[0010] Patent CN101675904A: Provides an additional device, which installs a membrane-like braid on the existing aortic endograft to ensure blood supply to the branch vessels and strengthen the stent. However, this device itself does not play a supporting role on the aortic endograft and is not suitable for aortic dissection areas with fewer branch vessels.

[0011] Patent CN204306860U Spring sheath occlusion: The spring sheath is placed at the end of the stent graft to seal any potential leakage points. However, in a high-pressure blood flow environment, the spring sheath is prone to migrate to non-target areas, causing new blood vessel blockage or organ ischemia; and its precise positioning is difficult.

[0012] Existing technology mostly uses metal stents in aortic surgery. Metal is non-degradable and may cause stent migration or re-leakage in the aortic cavity over a long period of time, increasing the risk of injury. Metal can cause excessive burden on blood vessels and increase the risk of long-term aortic true lumen thrombosis. The released metal ions can easily cause local inflammatory reactions.

[0013] Researching a shape and size that matches the aorta, which can relieve the patient's pain, be effective in function, provide firm support, have a suitable biodegradable time for human absorption, eliminate the risk of endoleakage in the aorta, the risk of retrograde aortic dissection, and provide a safe additional stent structure, has become a difficult problem to be tackled by scientific and technological personnel in this field. Summary of the invention

[0014] The utility model discloses an aortic stent structure made of absorbable polyester material, so as to solve the problems that the shape and size of the polyester polymer material biodegradable human body absorbable stent of the coronary artery in the prior art are not matched with the aortic blood vessel, and a new additional stent structure is urgently needed which can relieve the pain of patients, has effective functions, and eliminates the risks of aortic blood vessel leakage and reverse aortic dissection.

[0015] The utility model discloses an aortic stent structure made of absorbable polyester material, and the technical solution is as follows:

[0016] It is made of absorbable high molecular polyester material; the absorbable high molecular polyester material is extruded into a tubular tube with an outer diameter of 22 to 46 mm; the tube wall thickness is 0.4 to 1.5 mm; the tube is laser engraved to form an absorbable bare stent with a mesh; the diameter of the mesh is the same as the wall thickness of the absorbable polyester tube; the length of the tubular additional stent is 60 to 180 mm.

[0017] The first optimized solution is: the tube is laser engraved to form an absorbable bare stent with a Z-shaped and bridge-shaped mesh; the Z-shaped and bridge-shaped Z-shaped structure has an angle of 30 to 120 degrees between the two sides, a length of 6 to 18 mm, and a length of 6 to 18 mm for the bridge structure. The additional stent structure of the Z-shaped and bridge-shaped mesh increases the stability of the structure and reduces the risk of stent displacement; it is suitable for situations where the blood vessel has a high risk of displacement or the lesion site requires high stability support.

[0018] The second optimized solution is that the tube is laser engraved to form an absorbable bare stent with a honeycomb mesh; the honeycomb diameter is 3 to 7 mm, the honeycomb wall spacing is 0.5 to 2.5 mm, and the honeycomb depth is 1.0 to 5.0 mm. The additional stent structure of the honeycomb mesh provides highly uniform support while allowing good blood perfusion; it is suitable for extensive lesions that require uniform support while maintaining blood perfusion.

[0019] The third optimized solution is that the tube is laser engraved to form an absorbable bare stent with an elliptical mesh; the long axis of the ellipse is 8 to 20 mm and the short axis is 4 to 10 mm. The additional stent structure of the elliptical mesh provides a tighter fit to the vascular wall, which is suitable for lesions with irregular vascular morphology and helps improve the tightness of the vascular lining.

[0020] The fourth optimized solution is: the tube is laser engraved to form an absorbable bare stent with a diamond mesh; the diamond side length is 6 to 15 mm, and the angle of each diamond angle is 45 to 60 degrees. The additional stent structure of the diamond mesh provides uniform support, which helps to evenly disperse blood flow pressure and reduce stress concentration on the local blood vessel wall. It is suitable for lesion areas with relatively consistent blood vessel diameters and no obvious expansion or stenosis, such as certain types of aneurysms or vascular stenosis lesions.

[0021] The fifth optimized solution is: the tube is laser engraved to form an absorbable bare stent with a wavy mesh; the wavy amplitude is 5 to 10 mm and the wavelength is 8 to 16 mm. The additional stent structure of the wavy mesh allows a certain degree of flexibility and elasticity to adapt to the natural pulsation of the blood vessel; it is suitable for areas where the blood vessel flexibility needs to be maintained, such as areas with more blood vessel bends.

[0022] The sixth optimized solution is: the tube is laser engraved to form an absorbable bare stent with a spiral sinusoidal mesh; the spiral sinusoidal pitch is 10 to 18 mm, the amplitude is 6 to 9 mm, and the spiral is 5 to 7 complete sinusoidal waveforms per week. The additional stent structure of the spiral sinusoidal curve provides continuous support while allowing the stent to be flexibly extended in the longitudinal direction; it is suitable for long-segment lesions that need to maintain vascular continuity and avoid twisting.

[0023] Each shape is adapted to the specific characteristics of vascular lesions and surgical requirements to ensure the best treatment effect. Doctors usually decide on the mesh shape and develop the most appropriate treatment plan based on the results of imaging examinations (such as CT, MRI or angiography), the patient's specific condition, the anatomical characteristics of the lesion, clinical experience, expected treatment effects and the physical properties of the stent.

[0024] The utility model also comprises a surface coating layer; in addition to the solvent tetrahydrofuran, the coating solution of the coating layer also comprises polylactic acid degradable materials, drugs and active factors with anti-inflammatory and vascular endothelialization promoting effects, and contrast agents.

[0025] Preferably, the anti-inflammatory and endothelialization-promoting drugs include: one or more of rapamycin (0.1% to 1%), RGD peptide (0.005% to 0.25%), VEGF (0.0045% to 0.027%), chondroitin sulfate (0.1% to 2%), chitosan (0.5% to 2%), blue copper peptide (0.01% to 0.5%), paclitaxel (0.1% to 1%), simulos (0.01% to 0.02%), citric acid (0.1% to 2%), ibuprofen (0.1% to 1%), phosphatidylcholine (0.1% to 2%), and sodium hyaluronate (0.1% to 1%).

[0026] Preferably, the contrast agent comprises one or more of iopromide, diatrizoate, ioversol and diatrizoate (10% to 20%).

[0027] The manufacturing method of the aortic stent structure made of absorbable polyester material described in the utility model is as follows;

[0028] The first step is to select absorbable polyester materials and material blends; the selected absorbable polyester materials include one or more of polylactic acid, polyglycolide, polydioxanone and poly-ε-caprolactone, or a copolymer of two or three substances selected from polylactic acid, polyglycolide and poly-ε-caprolactone; the number average molecular weight range of the absorbable polyester material is 30,000 to 600,000 Daltons, and the molecular weight distribution index of the absorbable polyester material is 1.01 to 3.

[0029] The second step is tube extrusion. The absorbent polymer polyester material is extruded into a tube through a ring die in a screw extruder. The processing temperature of the screw extruder is between 85 and 230 degrees Celsius, and the screw speed is controlled at 20 to 120 revolutions per minute during the tube extrusion process.

[0030] The third step is laser engraving to form a mesh;

[0031] The fourth step is coating application.

[0032] The positive effects of the utility model are: completing the preliminary exploration of the application value of fully absorbable stents in the field of aortic diseases; applying the tube squeezing-laser engraving method to the field of large-sized aortic stent preparation; providing suitable mechanical support for the aortic covered stent as an additional stent, meeting the strength and toughness and human absorption and degradation requirements; matching the shape and size with the aortic blood vessels, which can reduce the pain of patients and be effective in function, eliminating the risk of aortic vascular leakage and reverse aortic dissection; unique materials, structures and designs, maximizing the adaptation to specific vascular lesion characteristics and surgical needs to ensure the optimization of treatment effects; providing doctors with the most suitable optional additional stent structure scheme for treatment based on the results of CT or MRI or angiography imaging examinations, combined with clinical experience and the physical properties of the stent. The stent surface is provided with a corrosion-inhibiting coating and active factors, which are conducive to promoting the proliferation of aortic vascular endothelial cells. The setting of the coating enables the absorbable bare stent of the utility model to have one or more effects of developing, anti-inflammatory and promoting endothelialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 This is a schematic diagram of the reverse Z-shaped and bridge-shaped mesh wire structure of the utility model;

[0034] Figure 2 This is a schematic diagram of the parallel Z-shaped and bridge-shaped mesh wire structure of the utility model;

[0035] Figure 3This is a schematic diagram of the honeycomb mesh structure of the utility model;

[0036] Figure 4 This is a schematic diagram of the elliptical mesh structure of the utility model;

[0037] Figure 5 This is a schematic diagram of the diamond mesh structure of the utility model;

[0038] Figure 6 This is a schematic diagram of the wavy mesh structure of the utility model;

[0039] Figure 7 This is a schematic diagram of the spiral sinusoidal mesh structure of the utility model;

[0040] Figure 8 This is the first set of flat plate compression support force test data diagram of the utility model;

[0041] Fig. 9 This is the second set of flat plate compression support force test data diagram of the utility model;

[0042] Fig.10 This is a test chart of the cell staining method for analyzing the biocompatibility of the cell surface of the material of the first embodiment;

[0043] Fig.11 This is a test chart of the cell staining method for analyzing the biocompatibility of the cell surface of the material of the first embodiment;

[0044] In the figure: 1 mesh filaments, 2 parallel bridge filaments; a cells were cultured for 1 day; b cells were cultured for 3 days; c cells were cultured for 5 days; d cells were cultured for 1 day; e cells were cultured for 3 days; f cells were cultured for 5 days. DETAILED DESCRIPTION

[0045] Several embodiments of the present utility model are described in detail below with reference to the accompanying drawings.

[0046] The first embodiment of the present utility model Figure 1 , Figure 2 As shown, in the first step, the absorbable polyester material is selected as L-polylactic acid; 1000 grams of L-polylactic acid with a number average molecular weight of 130,000 Daltons and a molecular weight distribution of 1.4 is placed in a 70-degree Celsius oven for drying; in the second step, the L-polylactic acid absorbable polyester material is added to a screw extruder, and extruded at 190 degrees Celsius at a rate of 30 revolutions per minute, and the outer diameter of the absorbable polyester tube is set to 40 mm and the tube wall thickness is 0.75 mm; and the absorbable polyester tube is cut to a length of 70 mm; in the third step, the absorbable polyester tube is placed in a laser engraving machine, and the bare stent structure information file is imported into the laser engraving machine for engraving to form a Figure 1 , Figure 2The absorbable bare stent with a Z-shaped and bridge-shaped mesh structure shown in the figure; in the Z-shaped and bridge-shaped Z-shaped structure, the diameters of the mesh 1 and the bridge 2 are the same as the wall thickness of the absorbable polyester tube; the angle between the two sides is 30 to 120 degrees, the length is 6 to 18 mm, and the length of the bridge structure is 6 to 18 mm; the fourth step is to immerse the prepared stent in a coating solution for 10 seconds; the solvent is tetrahydrofuran, and the solute includes 85% by mass of poly(L-lactic acid), 1% by mass of rapamycin and 1% by mass of chondroitin sulfate, and 13% by mass of iopromide; the coating solution is 10% by mass of the solute, and then taken out and dried.

[0047] In the second embodiment of the present utility model, in the first step, the absorbable polyester material is selected as L-polylactic acid and polyglycolide-lactide; in the second step, 800 grams of L-polylactic acid with a number average molecular weight of 90,000 Daltons and a molecular weight distribution of 2.1 and 200 grams of polyglycolide-lactide with a number average molecular weight of 60,000 Daltons and a molecular weight distribution of 1.5 are added to a screw extruder, and the extrusion is performed at a speed of 40 revolutions per minute at 210 degrees Celsius; the outer diameter of the absorbable polyester tube is set to 26 mm and the wall thickness is 0.4 mm; and the absorbable polyester tube is cut to a length of 100 mm; in the third step, the absorbable polyester tube is placed in a laser engraving machine, and the bare stent structure information file is imported into the laser engraving machine for engraving to form a tube as shown in FIG. Figure 3 The absorbable bare stent with a honeycomb mesh structure shown in the figure; the diameter of mesh 1 is the same as the wall thickness of the absorbable polyester tube; the honeycomb diameter is 3-7 mm, the honeycomb wall spacing is 0.5-2.5 mm, and the honeycomb depth is 1.0-5.0 mm; the fourth step is to immerse the prepared stent in a coating solution for 20 seconds; the solvent is tetrahydrofuran, and the solute includes 83% by mass of poly(L-lactic acid), 1% by mass of rapamycin and 1% by mass of chitosan, as well as 15% diatrizoate; the coating solution is composed of a solute mass fraction of 10%; and then taken out and dried.

[0048] The third embodiment of the utility model, in the first step, selects polydioxanone as the absorbable polyester material; puts 1000 grams of polydioxanone with a number average molecular weight of 80,000 Daltons and a molecular weight distribution of 1.3 into a 70 degree Celsius oven for drying; in the second step, the polydioxanone absorbable polyester material is added to a screw extruder, and extrudes the tube at a speed of 30 revolutions per minute under the condition of 130 degrees Celsius; sets the outer diameter of the absorbable polyester tube to 40 mm and the tube wall thickness to 0.75 mm; and cuts the absorbable polyester tube to a length of 70 mm; in the third step, puts the absorbable polyester tube into a laser engraving machine, imports the bare stent structure information file into the laser engraving machine for engraving, and forms a Figure 5The absorbable bare stent with a diamond mesh structure shown in the figure; the diameter of mesh 1 is the same as the wall thickness of the absorbable polyester tube; the side length of the diamond is 6 to 15 mm, and the angle of each diamond angle is 45 to 60 degrees; the fourth step is to immerse the prepared stent in a coating solution for 10 seconds; the solvent is tetrahydrofuran, and the solute includes 84% ​​by mass of poly(L-lactic acid), 0.5% by mass of rapamycin, 2% by mass of chitosan, and 13.5% by mass of ioversenin; the coating solution has a solute mass fraction of 10%; then it is taken out and dried.

[0049] In the fourth embodiment of the utility model, in the first step, the absorbable polyester material is selected as poly-ε-caprolactone; 1000 grams of poly-ε-caprolactone with a number average molecular weight of 90,000 Daltons and a molecular weight distribution of 1.5 is placed in a 40-degree Celsius oven for drying; in the second step, the poly-ε-caprolactone absorbable polyester material is added to a screw extruder, and extruded at a speed of 30 revolutions per minute at 85 degrees Celsius; the outer diameter of the absorbable polyester tube is set to 40 mm and the wall thickness is 0.75 mm; and the absorbable polyester tube is cut to a length of 70 mm; in the third step, the absorbable polyester tube is placed in a laser engraving machine, and the bare stent structure information file is imported into the laser engraving machine for engraving to form a Figure 7 The absorbable bare stent with a spiral sinusoidal mesh structure shown in the figure; the diameter of mesh 1 is the same as the wall thickness of the absorbable polyester tube; the spiral sinusoidal mesh has a spiral pitch of 10 to 18 mm, an amplitude of 6 to 9 mm, and 5 to 7 complete sinusoidal waveforms per spiral; the fourth step is to immerse the prepared stent in a coating solution for 10 seconds; the solvent is tetrahydrofuran, and the solute includes 85% by mass of poly(L-lactic acid), 1% by mass of rapamycin and 1% by mass of chondroitin sulfate, and 13% by mass of iopromide; the mass fraction of the solute in the coating solution is 10%; after the stent is immersed, it is taken out and dried.

[0050] The bare stents prepared in the first, second, third and fourth embodiments were tested for flat plate extrusion support force. The testing instrument was a WSM-20kN electronic universal material testing machine. During the test, the stent was compressed at a rate of 5mm / min. The stent to be tested was placed between the chuck plates of the tensile testing machine. The upper and lower chucks of the tensile testing machine were manually adjusted to compress it. The compression increment was 1 mm, and the support force was recorded. The test results are shown in the attached figure. Figure 8 shown.

[0051] The fifth embodiment of the utility model; the first step is to select the absorbable polyester material as L-polylactic acid and polyglycolide-lactide; the second step is to add 600 grams of L-polylactic acid with a number average molecular weight of 110,000 Daltons and a molecular weight distribution of 1.7 and 400 grams of polyglycolide-lactide with a number average molecular weight of 80,000 Daltons and a molecular weight distribution of 1.3 into a screw extruder, and extrude the tube at a speed of 50 revolutions per minute at 185 degrees Celsius, setting the outer diameter of the absorbable polyester tube to 27 mm and the wall thickness to 0.45 mm; and cut the absorbable polyester tube to a length of 110 mm; the third step is to put the absorbable polyester tube into a laser engraving machine, import the bare stent structure information file into the laser engraving machine for engraving, and form a tube as shown in FIG. Figure 4 The absorbable bare stent with an elliptical mesh structure shown in the figure; the diameter of mesh 1 is the same as the wall thickness of the absorbable polyester tube; the major axis of the ellipse is 8-20 mm, and the minor axis is 4-10 mm; in the fourth step, the prepared stent is immersed in the coating solution for 2 minutes; the solvent is tetrahydrofuran, and the solute includes 84% ​​by mass of poly-L-lactic acid, 0.5% by mass of rapamycin, 2% by mass of chitosan, and 13.5% by mass of ioversenin; the mass fraction of the solute is 10%, and then taken out and dried.

[0052] The sixth embodiment of the utility model; the first step is to select the absorbable polyester material as L-polylactic acid and polydioxanone; the second step is to add 500 grams of L-polylactic acid with a number average molecular weight of 110,000 Daltons and a molecular weight distribution of 1.2 and 500 grams of polydioxanone with a number average molecular weight of 100,000 Daltons and a molecular weight distribution of 2.5 into a screw extruder, and extrude the tube at a speed of 100 revolutions per minute at 190 degrees Celsius, setting the outer diameter of the absorbable polyester tube to 28 mm and the wall thickness to 0.5 mm; and cut the absorbable polyester tube to a length of 120 mm; the third step is to put the absorbable polyester tube into a laser engraving machine, import the bare stent structure information file into the laser engraving machine for engraving, and form a Figure 6 The absorbable bare stent with a wavy mesh structure shown in the figure; the diameter of mesh 1 is the same as the wall thickness of the absorbable polyester tube; the wavy amplitude of the wavy mesh structure is 5-10 mm, and the wavelength is 8-16 mm; the fourth step is to immerse the prepared stent in the coating solution for 10 seconds; the solvent is tetrahydrofuran, and the solute includes 86% by mass of poly(L-lactic acid), 2% by mass of citric acid, and 12% by mass of ioversenin; the mass fraction of the solute is 10%, and then taken out and dried.

[0053] The seventh embodiment of the utility model; the first step is to select the absorbable polyester material as L-polylactic acid and poly-ε-caprolactone; the second step is to add 300 grams of L-polylactic acid with a number average molecular weight of 80,000 Daltons and a molecular weight distribution of 1.9 and 700 grams of poly-ε-caprolactone with a number average molecular weight of 100,000 Daltons and a molecular weight distribution of 2.2 into a screw extruder, and extrude the tube at a speed of 25 revolutions per minute at 210 degrees Celsius, setting the outer diameter of the absorbable polyester tube to 29 mm and the wall thickness to 0.75 mm; and cut the absorbable polyester tube to a length of 170 mm; the third step is to put the absorbable polyester tube into a laser engraving machine, import the bare stent structure information file into the laser engraving machine for engraving, and form a tube as shown in FIG. Figure 7 The absorbable bare stent with a spiral sinusoidal mesh structure shown in the figure; the diameter of mesh 1 is the same as the wall thickness of the absorbable polyester tube; the spiral sinusoidal mesh has a spiral pitch of 10 to 18 mm, an amplitude of 6 to 9 mm, and 5 to 7 complete sinusoidal waveforms per spiral; the fourth step is to immerse the prepared stent in a coating solution for 30 seconds, the solvent is tetrahydrofuran, the solute includes 82% by mass of poly(L-lactic acid), 1% by mass of rapamycin, 2% by mass of phosphatidylcholine, and 15% by mass of iopromide; the mass fraction of the solute is 10%, and then the stent is taken out and dried.

[0054] The eighth embodiment of the utility model; the first step is to select polydioxanone and poly-ε-caprolactone as absorbable polyester materials; the second step is to add 200 grams of polydioxanone with a number average molecular weight of 80,000 Daltons and a molecular weight distribution of 1.8 and 800 grams of poly-ε-caprolactone with a number average molecular weight of 60,000 Daltons and a molecular weight distribution of 2.3 into a screw extruder, and extrude the tube at a speed of 95 revolutions per minute at 220 degrees Celsius, setting the outer diameter of the absorbable polyester tube to 31 mm and the wall thickness to 0.4 mm; and cut the absorbable polyester tube to a length of 165 mm; the third step is to put the absorbable polyester tube into a laser engraving machine, import the bare stent structure information file into the laser engraving machine for engraving, and form a tube as shown in FIG. Figure 3 The absorbable bare stent with a honeycomb mesh structure shown in the figure; the diameter of mesh 1 is the same as the wall thickness of the absorbable polyester tube; the honeycomb diameter is 3-7 mm, the honeycomb wall spacing is 0.5-2.5 mm, and the honeycomb depth is 1.0-5.0 mm; in the fourth step, the prepared stent is immersed in the coating solution for 30 seconds; the solvent is tetrahydrofuran, and the solute includes 85.5% by mass of poly-lactic acid, 1% by mass of paclitaxel and 0.5% by mass of blue copper peptide, as well as 13% diatrizoate, and the solute mass fraction is 10%, and then taken out and dried.

[0055] The ninth embodiment of the utility model; the first step is to select the absorbable polyester material as polyglycolide-lactide; 1000 grams of polyglycolide-lactide with a number average molecular weight of 30,000 Daltons and a molecular weight distribution of 1.3 is placed in a 90-degree Celsius oven for drying; the second step is to add the polyglycolide-lactide absorbable polyester material to a screw extruder, and extrudes the tube at a speed of 40 revolutions per minute at 215 degrees Celsius, setting the outer diameter of the absorbable polyester tube to 30 mm and the tube wall thickness to 0.5 mm; and cut the absorbable polyester tube to a length of 105 mm; the third step is to put the absorbable polyester tube into a laser engraving machine, import the bare stent structure information file into the laser engraving machine for engraving, and form a structure as shown in FIG. Figure 6 The absorbable bare stent with a wavy mesh structure shown in the figure; the diameter of mesh 1 is the same as the wall thickness of the absorbable polyester tube; the wavy amplitude of the wavy mesh structure is 5-10 mm, and the wavelength is 8-16 mm; the fourth step is to immerse the prepared stent in a coating solution for 20 seconds; the solvent is tetrahydrofuran, and the solute includes 82.5% by mass of poly-L-lactic acid, 0.25% by mass of RGD peptide, 0.02% by mass of VEGF and 0.23% by mass of chondroitin sulfate, and 17% by mass of diatrizoate; the mass fraction of the solute is 10%, and then taken out and dried.

[0056] The bare stents obtained in the fifth, sixth, seventh, eighth and ninth embodiments were subjected to a flat plate extrusion support force test. The test instrument was a WSM-20kN electronic universal material testing machine. During the test, the stent was compressed at a rate of 5mm / min. The stent to be tested was placed between the chuck plates of the tensile testing machine. The upper and lower chucks of the tensile testing machine were manually adjusted to compress it. The compression increment was 1 mm, and the support force was recorded. The test results are shown in the attached figure. Fig. 9 The supporting force of the ninth embodiment is significantly enhanced, and when the compression degree is 50%, the supporting force is 2.5 Newtons.

[0057] It can be seen from the data results that the embodiments of the utility model all have strong extrusion support capabilities and good mechanical properties, and can meet the mechanical requirements of aortic vascular stents; and the absorbable bare stent material formulas in embodiments five, six, seven, eight, and nine are different, providing stents with different support strengths and mechanical properties to meet the needs of different aortic disease patients for vascular stents.

[0058] like Fig.10 , Fig.11 As shown, the biocompatibility test of the scaffolds prepared in the first embodiment and the second embodiment was performed: the cell compatibility of the material surface was analyzed by using the Live-dead cell staining method, and the scaffold material was cut into sheets (1×1 cm 2 ) were used as samples to culture a certain number of human aortic endothelial cells (5×10 4), record the cell growth after 1 day, 3 days and 5 days, stain the live cells with calcein-AM (green fluorescence), and the dead cells with electrochemical propidium (red fluorescence); First Example Material Surface Cell Biocompatibility Cell Staining Analysis, 1 day, 3 days, 5 days test graph as shown Fig.10 Figure a shows the cell culture for 1 day; Figure b shows the cell culture for 3 days; Figure c shows the cell culture for 5 days. Fig.10 Figure d shows the cells cultured for 1 day; Figure e shows the cells cultured for 3 days; Figure f shows the cells cultured for 5 days. The biocompatibility requirements are met.

[0059] The listed structures are only part of the support structures of the utility model, not all of them. Based on these basic structures, all other support structures obtained by ordinary technicians in this field without creative work are within the scope of protection of the utility model.

Claims

1. An aortic stent structure made of absorbable polyester material, characterized in that: Tubular, with an outer diameter of 22~46 mm; wall thickness of 0.4~1.5 mm; with laser-engraved mesh; the mesh wire diameter is the same as the wall thickness of the absorbable polyester tube; length is 60~180 mm.

2. The aortic stent structure made of absorbable polyester material according to claim 1, characterized in that: The mesh wire engraved by the laser is a Z-shaped parallel bridge structure, the angle between the two sides of the Z-shaped structure is 30 to 120 degrees, the length is 6 to 18 mm, and the length of the parallel bridge structure is 6 to 18 mm.

3. The aortic stent structure made of absorbable polyester material according to claim 1, characterized in that: The laser engraved mesh wire is a honeycomb mesh wire structure; the honeycomb diameter is 3 to 7 mm, the honeycomb wall spacing is 0.5 to 2.5 mm, and the honeycomb depth is 1.0 to 5.0 mm.

4. The aortic stent structure made of absorbable polyester material according to claim 1, characterized in that: The mesh wire engraved by the laser is an elliptical mesh wire structure; the long axis of the ellipse is 8 to 20 mm, and the short axis is 4 to 10 mm.

5. The aortic stent structure made of absorbable polyester material according to claim 1, characterized in that: The mesh wire for laser engraving is a diamond mesh wire structure; the side length of the diamond is 6 to 15 mm, and the angle of each diamond corner is 45 to 60 degrees.

6. The aortic stent structure made of absorbable polyester material according to claim 1, characterized in that: The mesh wire engraved by the laser is a wavy mesh wire structure; the wavy amplitude is 5 to 10 mm and the wavelength is 8 to 16 mm.

7. The aortic stent structure made of absorbable polyester material according to claim 1, characterized in that: The mesh wire for laser engraving is a spiral sinusoidal mesh wire structure; the spiral sinusoidal pitch is 10 to 18 mm, the amplitude is 6 to 9 mm, and there are 5 to 7 complete sinusoidal waveforms per spiral.

8. The aortic stent structure made of absorbable polyester material according to claim 1, characterized in that: The invention also comprises a coating layer of a surface solvent tetrahydrofuran, a polylactic acid-based degradable material, drugs and active factors having anti-inflammatory and vascular endothelialization promoting effects, and a contrast agent.

Citation Information

Patent Citations

  • Self-protuberant aortic intracavity implant

    CN101675904A

  • Thoracic aorta covered stent with degradable bare area

    CN110721007A

  • Fixing and plugging device for aortic dissection minimally invasive operation

    CN204306860U